Documentos oficiais do RS para o ensino de língua portuguesa na voz de professores elaboradores e receptores - Nascimento, Silvana Schwab do (2015)
This study aimed to analyze the production and reception of two official Portuguese Language teaching documents produced in the state of Rio Grande do Sul entitled Educação para crescer: Projeto Melhoria da Qualidade de Ensino (1991-1995) and Referencial Curricular Lições do Rio Grande (2009) in order to discuss the meaning of the preparation and reception of these documents in different periods of the history of Portuguese Language teaching in that state, based on the object of analysis (interviews with the professors who developed and received these documents). This objective arises toward the main question of this research, namely, what relationships have been established in the last two decades between the state and Portuguese language teaching under the action of official documents to change the course of this school subject? The realization of this research came from Bakhtin‟s dialogical socio-historical theoretical perspective, which guided the analysis and the attribution of meanings of oral interviews with professors who developed and received such documents. Based on the theory adopted, we elected the following categories of analysis: chronotope of preparation and evaluation to the developers‟ group; chronotope of development and evaluation to the group of receivers. The work from these categories has allowed to clarify the process of preparation and reception of these documents; to know, from the developers‟ and receivers‟ words, the relations established between the state, the research subjects and possible Portuguese language teaching course changes from such relationships; to see the articulation of developers‟ and receivers‟ words, and to what extent this articulation allows us to understand the action of the state in the process of preparation and reception of official documents in two different periods of Portuguese language teaching in Rio Grande do Sul. After analyzing and attributing meaning to the interviewees saying we found that the relationship established between the state and the Portuguese Language teaching under the action of official documents to change the course of education was very similar both in Projeto Melhoria and Lições do Rio Grande. The effects of the implementation basically followed the same course, the same strategies, which resulted in abandoning and forgetting these documents when changing from one government to another. The state basically served as a trigger, as the creator of the process for developing the official documents, by acting in the direction of the university through the presence of professors to draw up these documents, delegating to them the task, but not interfering in the process. This research helped identify a stage of the history of education of Portuguese Language teaching in Rio Grande do Sul in connection with the publication of official documents and signaled the importance of giving a voice mainly to the professors who receive these documents, because the analysis showed that this professional has a lot to say about the experience with official documents and their effects of implementation, which are relevant in the development of other official documents.